Identifying the Potential of Islamic Mataram Culinary Footprints for Gastronomic Tourism in Yogyakarta - Makiya, Kiki Rizki; Haryanto, Eko; Noviati, Fitria (Dinasti Research, 2025)
Food is an essential element of a tourist's travel experience, often becoming a key reference in planning itineraries. The concept of culinary tourism has developed into gastronomic tourism, which encompasses not only the local cuisines, but also the culture and history behind them. This trifecta of cuisine, culture and history, known as the Triangle Concept of Indonesia’s gastronomy, is often still under-utilizing the storytelling component required in presenting the cultural and historical aspect of food. The rich, delectable, and distinct cuisines of Yogyakarta are rooted in its steep cultural heritage, still providing a lot of untapped potentials to enhance its tourism initiatives. One of the most significant periods in Yogyakarta’s history was the era of the Islamic Mataram Kingdom, instrumental in shaping both the region and the nation’s identity. Many of Yogyakarta’s legendary cuisines can be traced back to this period in history. Following the trail and development of the Islamic Mataram Kingdom, this research sought to identify the cuisines from this era that could be formulated as potential gastronomic tourism attraction to further boost the development of the local tourism. This qualitative-exploratory research employed purposive and snowball sampling techniques. Data collection was done through interviews, Focus Group Discussions (FGD), observations, and compilation of documents. Data were analyzed using an inductive approach through classification, coding and reduction process. The research resulted in the identification of cuisines that were mapped out according to 5 historical periods of the Islamic Mataram Kingdom’s existence, each food category accompanied by culinary data, historical information, and cultural role/significance, in line with the Triangle Concept of Indonesia’s Gastronomy.